Effect of transcutaneous auricular vagus nerve stimulation on postoperative pain in patients undergoing laparoscopic cholecystectomy: study protocol for a single-centre, prospective, randomised, double-blind, controlled study - Ling Zhang; Qin Zhang; He Liu; Liang Yu; Ya Cao; Dongxu Wang; Zhonghua Li; Keyu Fan; Mingxia Liu; Jingqiu Wei; Qianrong Wang (BMJ Open)
Introduction Pain after laparoscopic cholecystectomy (LC) is different from open cholecystectomy, characterised by visceral pain, parietal pain and shoulder pain, which affects postoperative recovery in patients undergoing LC. Recent studies have demonstrated the clinical efficacy of transcutaneous auricular vagus nerve stimulation (taVNS) in both acute and chronic pain treatment. The objective of this study protocol is to investigate the efficacy of taVNS in alleviating postoperative pain following LC.Methods and analysis In this single-centre, prospective, randomised, double-blind and controlled study, we will enrol 88 participants, aged between 18 and 65 years, who are scheduled for elective LC, and they will be randomly assigned to either the taVNS group (group T) or the control group (group C). For the primary outcome, we will compare the difference in pain score 6 hours after LC assessed using the Numeric Rating Scale. For the secondary outcomes, we will compare the difference including Quality of Recovery-15, Self-rating Depression Scale, Pittsburgh Sleep Quality Index and Postoperative Nausea and Vomiting score.Ethics and dissemination The Ethics Committee of Huzhou Central Hospital granted approval for the study with approval number: 202301007–01. Dissemination will be via national anaesthesia conferences and publication in the peer-reviewed literature.Trial registration number ChiCTR2300068410.